RETRACTED: FEATURES OF CRISIS MANAGEMENT IN ENTERPRISES - K. D. Busygin; A. K. Busygin (Модернизация, инновация, развитие, 2015)
Retracted articleThe article considers the value of preventive management in modern conditions. The global fi nancial and economic crisis of 2008-2010. sharpened interest in the problems of crisis management. This interest is manifested at the level of individual businesses, and at the level of the economy as a whole. At the same time revealed a signifi cant drawback: the development of crisis management theory lags behind practice. Non-compliance of the existing theory to modern requirements leads to the fact that the known approaches are not based on theoretical positions and empirical evidence and best practices, and, consequently, do not diff er systematically, because of this requires further research in this direction. The analysis shows that crisis management is a complex control system, which has its own specifi c features. Feature development solutions in crisis situations caused by the fact that they can only wear improving change with the obligatory account the limiting parameters of sustainable livelihoods enterprise (structure funds, personnel, activity profi le, the main products, and others).